2014
DOI: 10.4149/av_2014_04_368
|View full text |Cite
|
Sign up to set email alerts
|

The flavonoid from Polygonum perfoliatum L. inhibits herpes simplex virus 1 infection

et al.

Abstract: Summary. -Herpes simplex virus 1 (HSV-1) is one of the most prevalent human pathogens in both industrialized and developing countries. This study was performed to analyze the antiviral activity of purified flavonoid from Polygonum perfoliatum l. against HSV-1 infection in vitro and in vivo. Flavonoid showed no inhibitory effect, when treated before virus infection, but it strongly inhibited viral replication and cell-to-cell spread which was vital for the virus's propagation. The therapeutic effect of the flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…(2010) tested the effect of P. perfoliatum extract against herpes simplex virus-1 (HSV-1) in vitro by MTT, and it was found that its ethanol extract and ethanol elution part of D101 macroporous resin had significant antiviral effect, which was similar to positive control drug acyclovir (ACV), and the virus inhibition rates were 78.10%, 75.2%, and 81.6%, respectively; taking rutin as the standard reference substance, the content of active extract was determined by aluminum nitrate complexation spectrophotometry, and the results showed that the content of flavonoids was more than 80%. Through further experimental studies, it was found that the flavonoids of P. perfoliatum had a strong inhibitory effect on the replication and intercellular transmission of HSV-1 virus ( Fan et al., 2011 ), and could significantly prolong the survival time and improve the survival rate of mice with encephalitis induced by HSV-1 infection ( Zhang et al., 2014 ). It is an effective method for the treatment of recurrent HSV-1 infection.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…(2010) tested the effect of P. perfoliatum extract against herpes simplex virus-1 (HSV-1) in vitro by MTT, and it was found that its ethanol extract and ethanol elution part of D101 macroporous resin had significant antiviral effect, which was similar to positive control drug acyclovir (ACV), and the virus inhibition rates were 78.10%, 75.2%, and 81.6%, respectively; taking rutin as the standard reference substance, the content of active extract was determined by aluminum nitrate complexation spectrophotometry, and the results showed that the content of flavonoids was more than 80%. Through further experimental studies, it was found that the flavonoids of P. perfoliatum had a strong inhibitory effect on the replication and intercellular transmission of HSV-1 virus ( Fan et al., 2011 ), and could significantly prolong the survival time and improve the survival rate of mice with encephalitis induced by HSV-1 infection ( Zhang et al., 2014 ). It is an effective method for the treatment of recurrent HSV-1 infection.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…e active ingredients of each herb in SBT were obtained using TCMSP (http://lsp.nwsuaf.edu.cn/tcmsp.php) [28], according to bioavailability (OB) ≥30% [20] and drug-likeness (DL) ≥0.18 [29], as well as TCMGeneDIT (http://tcm.lifescience.ntu. edu.tw/) [30] and related studies [31][32][33][34][35][36][37].…”
Section: Active Ingredients Database Buildingmentioning
confidence: 99%
“…It grows in farmland, roadside and valley wetlands at an altitude of 80–2300 m [ 11 ]. P. perfoliatum can be processed into delicious dishes, high-quality livestock and poultry feed, and has high medicinal value [ 12 ]. Modern scientific research shows that it contains flavonoid and their glycosides [ 12 ], alkaloids, quinones [ 13 ], saponins, triterpenes, essential oil [ 10 ] and has the effects of anti-inflammatory [ 14 ], antitumor, antiviral [ 15 ] and antibacterial [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…P. perfoliatum can be processed into delicious dishes, high-quality livestock and poultry feed, and has high medicinal value [ 12 ]. Modern scientific research shows that it contains flavonoid and their glycosides [ 12 ], alkaloids, quinones [ 13 ], saponins, triterpenes, essential oil [ 10 ] and has the effects of anti-inflammatory [ 14 ], antitumor, antiviral [ 15 ] and antibacterial [ 10 ]. Meawhile, P. perfoliatum has a significant protective effect on liver injury [ 16 ], but the mechanism is still unclear, which seriously hinders its further development and utilization.…”
Section: Introductionmentioning
confidence: 99%